Brown bowel syndrome: a rare complication in diseases associated with long-standing malabsorption - Albrecht, Heinz; Hagel, Alexander; De Rossi, Thomas; Rau, Tilman; Kirchner, Thomas; Neurath, Markus; Raithel, Martin (Digestion, 2014)
Longtime chronic malabsorption may among other things cause a lack of liposoluble vitamins. Vitamin E deficiency can lead to formation of lipofuscin aggregates. Its deficiency is also associated with an increased lipofuscinosis of the bowel, i.e. brown bowel syndrome.Systematic research via Medline on brown bowel syndrome, lipofuscinosis, and vitamin E deficiency was performed. We combined our own clinical experience and a review of the literature for this paper. Its goal is to inform about the possible consequences of severe malabsorption and brown bowel syndrome.Systematic data about the occurrence of severe malabsorption and brown bowel syndrome are rare. Only about 27 scientific reports can be found on this subject. Brown bowel syndrome is found mostly in conjunction with vitamin E deficiency and lipofuscinosis of the bowel. The clinical findings are caused by both malabsorption and lipofuscinosis. Case reports show a therapeutic effect of vitamin E.Vitamin deficiency caused by longtime chronic malabsorption can lead to the development of brown bowel syndrome, which is seen as the expression of lipofuscinosis of the bowel, and can cause further clinical disorders. Patients with malabsorption should therefore be monitored regarding their vitamin E levels.
EVALuna2:1837